Standardizing gross descriptions of skin lesions in common bottlenose dolphins (Tursiops truncatus) stranded in Southwest Florida, 2015–2019 - Ruth Y. Ewing; Meghan N. Sutton; Hada M. Herring; Molly R. Schubert; Denise M. Boyd; Jill L. Richardson; David S. Rotstein (Frontiers in Marine Science, 2023)
As the first line of defense, the integumentary system is critical in comprehensively evaluating dolphin morbidity during stranding response. Most published studies on skin lesions in bottlenose dolphins (Tursiops truncatus) lack standardized gross descriptions and methodologies for evaluating lesions. The primary objective of this study was to evaluate the effectiveness of an assessment matrix designed to consistently describe skin lesions based on a set of standardized gross description characteristics. The matrix was implemented by reviewing necropsy reports, histopathology reports, and photographs collected from bottlenose dolphins stranded in Southwest Florida from 2015 through 2019. Of the 32 dolphins that met the inclusion criteria, 19 presented with skin lesions and five reviewers described each of the 46 lesions according to a novel, standardized assessment matrix. The most common descriptor selected, in each of the respective matrix categories, were, by anatomic location, head; distribution, multifocal to coalescing; quantity, moderate (10–30); size, <2 cm; shape, punctate; margin, rounded; color modifier, hyperpigmentation; texture, smooth; and texture modifier, flat. These prevalent descriptors coincided with the frequent occurrence of histologically described hydropic degeneration (n=7, 15.2%) and were confirmed poxviral lesions in 6.52% (n=3). Identifying lesion patterns using standardized descriptors capitalizes on the unique pathogen tissue tropism and the implementation of certain disease mechanisms in the integumentary system. Therefore, it can facilitate differential disease diagnoses and guide ancillary diagnostics testing. The use of standardized descriptors will aid in etiologic identification and monitoring of skin lesions and associated diseases, advancing our understanding of dolphin morbidity and mortality.

Novel Lethal Clostridial Infection in Florida Manatees (Trichechus manatus latirostris): Cause of the 2013 Unusual Mortality Event in the Indian River Lagoon - Jan H. Landsberg; Maki Tabuchi; David S. Rotstein; Kuttichantran Subramaniam; Thais C. S. Rodrigues; Thomas B. Waltzek; Nicole I. Stacy; Patrick W. Wilson; Yasunari Kiryu; Francisco A. Uzal; Martine de Wit (Frontiers in Marine Science, 2022)
The Indian River Lagoon (IRL) on Florida’s east coast is a biologically diverse estuary and an important habitat to the threatened Florida manatee ( Trichechus manatus latirostris ). An unusual mortality event (UME) was declared by the Working Group on Marine Mammal Unusual Mortality Events in 2013 after a marked increase in manatee deaths in the IRL of an unknown cause. This UME followed a dramatic reduction of seagrass coverage in the IRL due to chronic non-toxic phytoplankton blooms, with a resultant ecosystem shift to mixed macroalgal dominance. At least 199 manatee deaths fitting the UME case definition were documented in and adjacent to the IRL during 2012–2019; mortality was highest in 2013, when 111 of these deaths were documented. The case definition included carcasses in good nutritional condition, with multiorgan congestion or wet lungs consistent with drowning without trauma. The gastrointestinal compartments of manatee carcasses were filled with diverse macroalga species, and the contents were notably more fluid than usual. Gross intestinal findings included blebbing to segmental thickening of the wall. Microscopic lesions were primarily intestinal, including necrosis, edema, hemorrhage, mucosa-associated lymphoid changes, and inflammation, sometimes associated with Gram-positive bacterial rods. A multidisciplinary approach of environmental and carcass sampling found no causative evidence through tests for micro- and macroalgal biotoxins, trace metals, general toxin screening, or vitreum biochemistry. Microbiological, cytological, immunohistochemical, and molecular analyses of Clostridiales from intestinal samples identified Clostridioides difficile toxin A, toxins A/B and toxin A gene; Paeniclostridium sordellii lethal gene (and other potential virulence factors from a sequenced strain); and Clostridium perfringens alpha and epsilon toxin genes. The results from this 8 year-long investigation are indicative that the cause of death in this manatee UME was associated with clostridial infection, initiated by a shift to a predominantly macroalgal diet.

Anthropogenic Contaminants and Histopathological Findings in Stranded Cetaceans in the Southeastern United States, 2012–2018 - Annie Page-Karjian; Catherine F. Lo; Branson Ritchie; Craig A. Harms; David S. Rotstein; Sushan Han; Sayed M. Hassan; Andreas F. Lehner; John P. Buchweitz; Victoria G. Thayer; Jill M. Sullivan; Emily F. Christiansen; et al. (Frontiers in Marine Science, 2020)

Novel Necropsy Findings Linked to Peracute Underwater Entrapment in Bottlenose Dolphins (Tursiops truncatus) - Alexandra L. Epple; Joanna T. Daniel; Susan G. Barco; David S. Rotstein; Alexander M. Costidis (Frontiers in Marine Science, 2020)

Suspected broadhead arrow injuries in two common bottlenose dolphins ( Tursiops truncatus ) along the Alabama Coast - Merri K. Collins; Ruth H. Carmichael; David S. Rotstein; Jason H. Byrd; Alissa C. Deming (Marine Mammal Science, 2020)

Systemic Edwardsiella tarda infection in a Western African lungfish ( Protopterus annectens ) with cytologic observation of heterophil projections - Estelle Rousselet; Nicole I. Stacy; David S. Rotstein; Tom B. Waltzek; Matt J. Griffin; Ruth Francis‐Floyd (Journal of Fish Diseases, 2018)
This report describes a case of systemic bacterial infection caused by Edwardsiella tarda in a Western African lungfish ( Protopterus annectens ) exposed to poor environmental and husbandry conditions. The fish presented with a large, external ulcerative lesion and died 2 weeks after developing anorexia. Histological evaluation revealed multifocal areas of necrosis and heterophilic and histiocytic inflammation throughout multiple tissues. Gram stain identified small numbers of intra‐ and extracellular monomorphic Gram‐negative 1 to 2 μm rod‐shaped bacilli. Cytology of lung granuloma, kidney and testes imprints identified heterophilic inflammation with phagocytosis of small monomorphic bacilli and some heterophils exhibiting cytoplasmic projections indicative of heterophil extracellular traps (HETs). Initial phenotypic analysis of isolates from coelomic fluid cultures identified E. tarda . Subsequent molecular analysis of spleen, liver and intestine DNA using an E . tarda ‐specific endpoint PCR assay targeting the bacterial fimbrial subunit yielded a 115 bp band. Sequencing and BLASTN search revealed the sequence was identical (76/76) to E . tarda strain FL 95‐01 (GenBank acc. CP011359 ) and displayed 93% sequence identity (66/71) to Edwardsiella hoshinae strain ATCC 35051 (GenBank acc. CP011359 ). This is the first report of systemic edwardsiellosis in a lungfish with concurrent cytologically identified structures suggestive of HETs.

Assessment of wound healing of tagged gray ( Eschrichtius robustus ) and blue ( Balaenoptera musculus ) whales in the eastern North Pacific using long‐term series of photographs - Stephanie A. Norman; Kiirsten R. Flynn; Alexandre N. Zerbini; Frances M. D. Gulland; Michael J. Moore; Stephen Raverty; David S. Rotstein; Bruce R. Mate; Craig Hayslip; Diane Gendron; Richard Sears; Annie B. Douglas; et al. (Marine Mammal Science, 2018)
Tags have been used to examine migration routes and habitat use of large whales for >40 yr, however, evaluation of tag wound healing has largely been short‐term, anecdotal or generalized. This study developed methods for systematic photographic assessment of long‐term external consequences of tag placement, to determine potential differences in wound healing between species and tag types and thus advise future tagging efforts to possibly minimize undesirable side effects. Tag site appearance and healing characteristics were evaluated by two reviewers and a time series evaluated by five veterinarians from photographs during 995 postdeployment encounters with 34 gray and 63 blue whales tagged in the North Pacific. Blue whale resightings were less frequent, but spanned a longer time period due to earlier tag deployments than the more frequent gray whale follow‐up observations. Swelling occurred in 74% of reencountered gray whales, with the highest frequency 6 mo postdeployment. Swellings were common in blue whales with early tag designs but rare with current models. Depressions occurred in 82% of gray and 71% of blue whales. This study demonstrates the value of follow‐up studies of tagged animals and systematic scoring of photographs to quantitatively compare tag response.

Prevalence and anatomic site of Crassicauda sp. infection, and its use in species identification, in kogiid whales from the mid‐Atlantic United States - Tiffany F. Keenan‐Bateman; William A. McLellan; Craig A. Harms; Marina A. Piscitelli; Susan G. Barco; Victoria G. Thayer; Gretchen N. Lovewell; Karen L. Clark; Paul K. Doshkov; David S. Rotstein; Charles W. Potter; D. Ann Pabst (Marine Mammal Science, 2016)
The parasitic nematode Crassicauda sp. was initially described in kogiid whales from specimens collected within cervical tissues, uncommon sites of infection for this parasite. Crassicauda sp. has only been reported in Kogia breviceps to date, but no study has yet investigated a large sample of both kogiid species. A 15 yr record of 104 kogiid strandings ( K. sima , n = 40; K. breviceps , n = 64) in North Carolina and Virginia, U.S.A. was used to determine the prevalence of Crassicauda sp. across species, within species across sex, and within sex across length and life history categories. Crassicauda sp. was confirmed to be a species‐specific parasite among kogiids infecting only K. breviceps (prevalence = 45%). Within K. breviceps , prevalence was similar (45%) in both immature and mature males, but increased from 10% in immature to 76% in mature females. This study confirmed the cervico‐thoracic distribution of the parasite, and identified a novel site of infection in a previously undescribed exocrine gland associated with the pigmented “false gill slit.” The species‐specific nature of Crassicauda sp. infection, the exocrine gland, and the distinct features of the false gill slit pigmentation associated with the gland, are all useful characters to identify kogiid species in the field.

Hematological, biochemical, and morphological parameters as prognostic indicators for stranded common dolphins ( Delphinus delphis) from Cape Cod, Massachusetts, U.S.A. - Sarah M. Sharp; Joyce S. Knoll; Michael J. Moore; Kathleen M. Moore; Charles T. Harry; Jane M. Hoppe; Misty E. Niemeyer; Ian Robinson; Kathryn S. Rose; W. Brian Sharp; David Rotstein (Marine Mammal Science, 2014)
The current paucity of published blood values and other clinically relevant data for short‐beaked common dolphins, Delphinus delphis, hinders the ability of veterinarians and responders to make well‐informed diagnoses and disposition decisions regarding live strandings of this species. This study examined hematologic, clinical chemistry, and physical parameters from 26 stranded common dolphins on Cape Cod, Massachusetts, in light of their postrelease survival data to evaluate each parameter's efficacy as a prognostic indicator. Statistically and clinically significant differences were found between failed and survived dolphins, including lower hematocrit, hemoglobin, TCO 2 , and bicarbonate and higher blood urea nitrogen, uric acid, and length‐to‐girth ratios in animals that failed. In general when compared to survivors, failed dolphins exhibited acidosis, dehydration, lower PCV s, and decreased body condition. Additionally, failed dolphins had the highest ALT , AST , CK , LDH , GGT , and lactate values. These blood values combined with necropsy findings indicate that there are likely a variety of factors affecting postrelease survival, including both preexisting illness and stranding‐induced conditions such as capture myopathy. Closer evaluation of these parameters for stranded common dolphins on point of care analyzers in the field may allow stranding personnel to make better disposition decisions in the future.

A Longman's beaked whale ( Indopacetus pacificus ) strands in Maui, Hawaii, with first case of morbillivirus in the central Pacific - Kristi L. West; Susan Sanchez; David Rotstein; Kelly M. Robertson; Sophie Dennison; Gregg Levine; Nicole Davis; David Schofield; Charles W. Potter; Brenda Jensen (Marine Mammal Science, 2013)

Rope trauma, sedation, disentanglement, and monitoring‐tag associated lesions in a terminally entangled North Atlantic right whale ( Eubalaena glacialis ) - Michael Moore; Russel Andrews; Trevor Austin; James Bailey; Alex Costidis; Clay George; Katie Jackson; Tom Pitchford; Scott Landry; Allan Ligon; William McLellan; David Morin; et al. (Marine Mammal Science, 2013)
A chronically entangled North Atlantic right whale, with consequent emaciation was sedated, disentangled to the extent possible, administered antibiotics, and satellite tag tracked for six subsequent days. It was found dead 11 d after the tag ceased transmission. Chronic constrictive deep rope lacerations and emaciation were found to be the proximate cause of death, which may have ultimately involved shark predation. A broadhead cutter and a spring‐loaded knife used for disentanglement were found to induce moderate wounds to the skin and blubber. The telemetry tag, with two barbed shafts partially penetrating the blubber was shed, leaving barbs embedded with localized histological reaction. One of four darts administered shed the barrel, but the needle was found postmortem in the whale with an 80º bend at the blubber‐muscle interface. This bend occurred due to epaxial muscle movement relative to the overlying blubber, with resultant necrosis and cavitation of underlying muscle. This suggests that rigid, implanted devices that span the cetacean blubber muscle interface, where the muscle moves relative to the blubber, could have secondary health impacts. Thus we encourage efforts to develop new tag telemetry systems that do not penetrate the subdermal sheath, but still remain attached for many months.

Shark predation on North Atlantic right whales ( Eubalaena glacialis ) in the southeastern United States calving ground - Jessica K. D. Taylor; John W. Mandelman; William A. McLellan; Michael J. Moore; Gregory B. Skomal; David S. Rotstein; Scott D. Kraus (Marine Mammal Science, 2013)

Presumed hyperglycemic cataracts in a live‐stranded minke whale ( Balaenoptera acutorostrata ) calf - Craig A. Harms; Gretchen N. Lovewell; David S. Rotstein (Marine Mammal Science, 2008)